Realidades e interrogantes en la relación entre Escocia y Reino Unido (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
The Unionist victory in the referendum of September 18 has meant only one point and followed as far as the territorial and constitutional configuration of the UK. Linking the promised reform to Scotland with the resolution of the West Lothian Question, as David Cameron pretends, can be interpreted in multiple keys, one of them undermine his Labour rival before of the 2015 elections. Meanwhile, the SNP it stands united and independence remains his main aspiration.
Keywords: Scotland; United Kingdom; Constitutional Reform; West Lothian Question; Independence; Unionismo; Labour Party; Conservative Party; Scottish National Party; Smith Commission; Strathclyde Commission